O assassinato de Violeta Formiga: a imprensa e a atuação do movimento feminista paraibano - Oliveira, Rayana Benício de (2017)
This work resumes the case of the murder of Violeta de Lourdes Formiga, a poet, born in the city of Pombal on May 28, 1951, who was murdered by her ex-husband, Antonio Olimpio Rosado Maia, in Tambaú, a neighborhood of the city of João Pessoa, on August 21, 1982. For the analysis of the case, I did contextualize the "crimes of honor", in which this case is inserted. I present to the readers the concept of feminicide, which according to Rita Laura Segato (2006) is a political term, since, feminicide is a crime of the patriarchy, with imposition of power, with the use of physical force; it is a crime of hate against women. In addition, this dissertation covers the various narratives of the Paraíba press, investigating the treatment of the Violeta Formiga case, on the pages of the newspapers. I will Throughout the text, I have observed the importance of the Feminist Movement in this case. This work belongs to the Research Line of History Teaching and Historical Knowledge.